Promoting Brain Health and Well-Being in Teacher Training Programs: A Case Study - Marikar, Faiz (Happiness: Journal of Psychology and Islamic Science, 2025)
The purpose of this study was to explore and evaluate the implementation of Life’s Ten Principles in the Certificate in Teaching in Higher Education (CTHE) program at General Sir John Kotelawala Defence University as a promotive and preventive effort to enhance brain health and mental well-being among early-career academics. This study also aimed to examine how the integration of brain health activities into the learning process could support professional development, improve teaching effectiveness, strengthen mental resilience, and create a healthy, happy, and productive learning environment. General Sir John Kotelawala Defence University pioneered preventive brain health and mental well-being by integrating Life’s Ten Principles into the Certificate in Teaching in Higher Education (CTHE) program during the 2024 Preventive Brain Health Week. The pilot program involved 40 early-career academics who participated in interactive lectures, practical sessions, and reflective teaching portfolios focusing on holistic lifestyle factors such as healthy eating, physical activity, sleep hygiene, stress management, metabolic health, and social engagement. The findings suggest that feedback from students and young academics was utilized to guide decisions regarding program improvement. Furthermore, participants reported that integrating brain health activities may support professional development, teaching effectiveness, and mental resilience, thereby contributing to a healthy, happy, and effective learning environment.